Seismic Behavior of Qinghai-Tibetan Railway Embankment in Permafrost Regions: A Case Study - Tuo Chen; Jianzhou Wang; Bo Wang (Shock and Vibration)
The temperature is a critical factor that determines the unfrozen water content and ice content in the frozen soil. In view of mechanical properties of the frozen soil depend on the volume of components of the four-phase systems, thus the temperature has a significant impact on the mechanical behaviors and deformation properties. The thermal state of the embankment in permafrost regions has a significant seasonal difference, then the seismic performance of the embankment alters with the season. In addition, the seismic performance is highly influenced by the properties of the earthquake motion, especially the seismic intensity. Combining these factors, a numerical simulation was conducted in this study. In this study, taking a typical section of Qinghai-Tibet Railway as an example, a numerical case study on the seismic behavior of embankment was carried out using the dynamic explicit FEM code ABAQUS/Explicit. The El Centro excitation with different intensities was performed in numerical analysis and two distinct thermal states of the embankment in extreme cold and warm days were considered as well. The seismic behaviors of the embankment, including the acceleration responses, the strain response, and the displacement response, were studied effectively. This paper proposes approaches and methods to study the seismic failure mechanism of the infrastructures, and the results can serve as a scientific basis for resisting earthquakes and preventing disasters in cold regions.